The caridean shrimps(Crustacea Decapoda) of the Albatross Philippine expedition, 1907-1910 part 4 families Oplophoridae and Nematocarcinidae - Chace, Fenner A., Jr. (Washington, D.C. Smithsonian Institution Press, 1986)
Smithsonian contributions to zoology; no.381
Keywords: Crustacea--Classification--Collected works; Crustacea--Philippines--Classification--Collected works; Shrimps--Philippines--Classification--Collected works